Pengaruh Implementasi Nilai Kebinekaan terhadap Pembentukan Perilaku Toleransi Siswa - Simanungkalit, Anita; Habeahan, Sampitmo (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The potential for the diversity of students at school to be developed to become individuals who have firm belief and devotion to God Almighty by displaying tolerant behavior. However, this tends not to be in accordance with issues in the learning process at school. The aim of this research is to determine the effect of implementing the value of diversity on the formation of students' tolerant behavior at Gajah Mada Private Middle School, Medan. The author applies quantitative research methods using a correlational approach. Applying descriptive quantitative research methods. Quantitative research involves two variables, namely x (implementation of diversity values) and y (student tolerance behavior). Data analysis in this research uses quantitative statistical methods through product moment calculations. The findings from the research stated that there was a 22.1% influence of the implementation of diversity values ​​on the formation of students' tolerant behavior at Gajah Mada Private Middle School, Medan. This is proven from the analysis of the correlation coefficient between variable x and variable y, obtaining a calculated r value of 0.470. If this value is compared with the rtable value at a significance level of 5% and n=31, therefore, rcount has a value in accordance with the provisions, if the profit is higher than rtable (rcount>rtable) or 0.470>0.355 so it can be concluded that there is The significant influence of the value of implementing diversity on the formation of students' tolerant behavior at Gajah Mada Private Middle School, Medan.